2021
DOI: 10.1038/s41598-021-91371-4
|View full text |Cite
|
Sign up to set email alerts
|

Atomic force microscopy analysis of native infectious and inactivated SARS-CoV-2 virions

Abstract: SARS-CoV-2 is an enveloped virus responsible for the Coronavirus Disease 2019 (COVID-19) pandemic. Here, single viruses were analyzed by atomic force microscopy (AFM) operating directly in a level 3 biosafety (BSL3) facility, which appeared as a fast and powerful method to assess at the nanoscale level and in 3D infectious virus morphology in its native conformation, or upon inactivation treatments. AFM imaging reveals structurally intact infectious and inactivated SARS-CoV-2 upon low concentration of formalde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 24 publications
3
50
0
Order By: Relevance
“…These data are quite desirable to promote the evaluation of new products, especially for disinfection purposes. The nanoindentation analysis also corroborated the suggestion made by Lyonnais et al, 23 confirming the deformable feature of the SARS-CoV-2. Finally, the most innovative result is that the SARS-CoV-2 virus may self-assemble after mechanical stress.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…These data are quite desirable to promote the evaluation of new products, especially for disinfection purposes. The nanoindentation analysis also corroborated the suggestion made by Lyonnais et al, 23 confirming the deformable feature of the SARS-CoV-2. Finally, the most innovative result is that the SARS-CoV-2 virus may self-assemble after mechanical stress.…”
Section: Resultssupporting
confidence: 87%
“…Their findings suggest that the spikes interspacing is ∼15 nm and they reported other densities spaced 5 to 8 nm apart, connecting the RNP (ribonucleoprotein complex: composed by the N protein and the genome) to the membrane region, but could not confidently affirm if these densities were related to M or N proteins. For the SARS-CoV-2, Kiss et al 22 and Lyonnais et al 23 reported a “bald” viral particle showing a smooth surface, without clear smaller structures. Opposingly, our data show that the viral particle membrane is crowded with smaller structures, suggesting the structural description of the proteins on the membrane surface.…”
Section: Resultsmentioning
confidence: 99%
“…Using FCS and PALM, we found a 120-140nm particle size range (Figure 2D,E) : 100-110 nm for MNE VLPs, and 130nm for MNES VLPs, which is consistent with AFM results (Figure 1D ). It is to notice that VLPs size are slightly bigger than wild-type virus particles as it has been described using AFM [19], TEM [19] or cryoET [27] [28] [29].…”
Section: Discussionmentioning
confidence: 99%
“…The purified MNE and MNES VLPs were next imaged by AFM in buffer for size and shape characterization (Figure 1D), in the conditions previously used for the wild-type virus [19]. We then determined the M(GFP)NES and M(GFP)NE VLPs size and approximate concentration using Fluorescence Correlative Microscopy (FCS) (Figure 2D).…”
Section: -Optimized Virus-like-particles Production By Mimicking Sars...mentioning
confidence: 99%
“…Ethical approval was obtained for the use of anonymized oropharyngeal specimens from patients for the diagnosis of SARS-CoV-2 (North West-Greater Manchester South Research Ethics Committee [REC], REC Ref:19/NW/0730). Specimens were maintained in Copan Universal Transport Medium (UTM) before being inactivated in a 1% final concentration of formaldehyde (Pierce) for 5 min at room temperature 51 , followed by clarification at 13,000× g for 5–10 min and diluted 1:10 in viral resuspension buffer (10 mM Tris HCl pH8, 100 mM NaCl) prior to use.…”
Section: Methodsmentioning
confidence: 99%